2013
DOI: 10.1051/0004-6361/201321345
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulations of near-surface convection in main-sequence stars

Abstract: Context. The atmospheres of cool main-sequence stars are structured by convective flows from the convective envelope that penetrate the optically thin layers and lead to structuring of the stellar atmospheres analogous to solar granulation. The flows have considerable influence on the 3D structure of temperature and pressure and affect the profiles of spectral lines formed in the photosphere. Aims. For the set of six 3D radiative (M)HD simulations of cool main-sequence stars described in the first paper of thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
51
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 33 publications
11
51
4
1
Order By: Relevance
“…The brightness enhancement of CBPs is the result of a side-wall heating in the interior of the vortices (see e.g. Beeck et al 2013). CBPs have a horizontal diameter of ∼ 80 km which is consistent with results in Moll et al (2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The brightness enhancement of CBPs is the result of a side-wall heating in the interior of the vortices (see e.g. Beeck et al 2013). CBPs have a horizontal diameter of ∼ 80 km which is consistent with results in Moll et al (2011).…”
Section: Discussionsupporting
confidence: 86%
“…The number of fragments rises with increasing granular diameter. In their MHD simulations, Beeck et al (2013) label the small cells as erroneous detections. In paper I we showed that small granules strongly contribute to the total number of detected granules, and hence, have a major influence on the dynamics of the population of all granules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, towards the limb some convective flows will be be hidden behind granules, which may result in a reduction in the line broadening induced by the LOS velocities and could decrease the FWHM (Beeck et al 2015b). However, one could also expect an increase in the FWHM because of an increasing contribution of the flows orthogonal to the granule peaks, since these flows have a higher variability than those parallel (Beeck et al 2013).…”
Section: Local Ccf Shape Across the Stellar Limbmentioning
confidence: 99%
“…To test whether this full apparatus was required, we performed this detailed analysis for the small (9 Mm in both horizontal directions, 3 Mm in the vertical direction) G2V solar simulations described in Beeck et al 2013b 20 . To save time for the purposes of the test, we used four snapshots separated in time by 19 minutes (making the radiative output essentially uncorrelated for these small boxes as the granulation structure has changed completely between any two snapshots).…”
Section: Granulation-driven Tsi Variabilitymentioning
confidence: 99%
“…This is a feasible task since a) reliable simulations of granulation patterns on main sequence stars are gradually becoming available 20,30 , b) new methods for extrapolating the magneticallydriven brightness variations from the Sun to Sun-like stars with various levels of magnetic activity observed at arbitrary angles between rotational axis and line-of-sight have been recently developed 6,28 .…”
mentioning
confidence: 99%